2020
DOI: 10.1093/conphys/coaa082
|View full text |Cite
|
Sign up to set email alerts
|

A blubber gene expression index for evaluating stress in marine mammals

Abstract: Evaluating the impacts of anthropogenic disturbance on free-ranging marine mammal populations, many of which are in decline, requires robust diagnostic markers of physiological stress and health. However, circulating levels of canonical ‘stress hormones’ such as glucocorticoids, which are commonly used to evaluate animal health, do not capture the complexity of species-specific responses and cannot be easily measured in large, fully aquatic marine mammals. Alternatively, expression of stress-responsive genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
4
11
0
Order By: Relevance
“…RNA integrity numbers (RIN) for muscle and blood samples were 8.93 ± 0.37 and 5.11 ± 1.26, respectively. RIN values for RNA isolated from muscle samples that were preserved in RNA later TM and those that were flash frozen in liquid nitrogen were comparable as shown previously ( Pujade Busqueta et al, 2020 ).…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…RNA integrity numbers (RIN) for muscle and blood samples were 8.93 ± 0.37 and 5.11 ± 1.26, respectively. RIN values for RNA isolated from muscle samples that were preserved in RNA later TM and those that were flash frozen in liquid nitrogen were comparable as shown previously ( Pujade Busqueta et al, 2020 ).…”
Section: Methodssupporting
confidence: 86%
“…RNA later TM was removed from samples prior to freezing at −80°C for long term storage. We previously showed that the integrity of RNA isolated from samples frozen in the field and those preserved in RNA later TM were comparable and can be used interchangeably for targeted gene expression analyses ( Pujade Busqueta et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships between environmental stressors such as pollutant and pathogen exposure and transcriptomic responses have been documented in a wide variety of taxa, including great tits [ 8 ], killifish ( Fundulus heteroclitus [ 73 ]), and wild salmon smolts ( Oncorhynchus nerka [ 74 ]). Additionally, correlations between stress hormones and gene expression have been documented in elephant seals ( Mirounga angustirostris [ 75 ]). Transcriptomic data can also be paired with sex or life stage information to explore the potential for developing gene expression-based biomarkers to determine important demographic information such as sex, which would be a useful addition to the current methods available for sexing immature marine turtles [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animals were sedated and sampled as described previously ( Debier et al, 2020 ; Pujade Busqueta et al, 2020 ). Briefly, seals were chemically immobilized using an intramuscular injection of ∼1 mg/kg tiletamine-zolazepam HCl (Telazol, Fort Dodge Animal Health, United States), and sedation was maintained with intravenous doses of ketamine (0.25–1 mg/kg) (Fort Dodge Animal Health, IA, United States).…”
Section: Methodsmentioning
confidence: 99%